EFFECT OF INSITU GREEN MANURING ON SOIL FERTILITY, GROWTH AND YIELD OF RICE UNDER ORGANIC FARMING - GANAPATHI and M.Y. ULLASA*, (The Journal of Research ANGRAU, 2019)
The experiment was conducted to study the effect of insitu green manuring on soil fertility, growth and yieldof rice under organic farming during kharif season for three consecutive years from 2012-13 to 2015-16.It wasobserved that the application of 100 kg Nequivalent FYM for preceding dhaincha (Sesbania aculeata) has producedhigher green biomass yield (21.55 t ha-1) as compared to other green manuring crops with or without manuring.Incorporation of green manuring crop fertilized with 100 kg N equivalent FYM along with recommended dose of FYM(10 t ha-1) for succeeding rice crop has recorded significantly higher growth, yield attributes, grain (50.49 q ha-1) andstraw yield (80.60 q ha-1). Also, the microbial population and final nutrient status of soil was found highest in thetreatment which received 100 kg N equivalent FYM for dhaincha crop during sowing along with application ofrecommended dose of FYM for rice (10 t ha-1) during incorporation of dhaincha. The continuous application of FYMalong with green manure for four consecutive years enhanced the soil chemical and biological properties.